Examining The Procedure of Food Processing for Hospital Patients - I Made Putra Kusuma Dana; Ida Bagus Teddy Prianthara (Institute of Computer Science (IOCS), 2021)
Hospital is as a complex, dynamic, competitive, capital intensive, labor intensive, and multi-disciplinary service organization. Various existing hospitals tried to gain the trust from the community by promoting efficient and quality services. Hospital food is often considered negative such as cold, tasteless, poor serving and poor service. Improving the quality of hospital food service is challenging, requiring the flow of processes to be understood from start to finish. This study aimed to develop a conceptual model in holistic manner along with deeper understanding management of patient meals at Bali Mandara Regional Hospital. The research method used is qualitative research method, data analysis in this study were using observations, interviews, and documentation which obtained from research as means of data reduction, data presentation, and conclusion drawing. Furthermore, to verify the data using Triangulation. The communication in management of food has been running well and effectively, human resources in the management of food are adequate, but the resources such as equipment and technology still needed to improve, the attitude of management serving food is good and the structure of managing food bureaucracy has known their respective duties and responsibilities. Based on results of the study, it showed that food administration and vital is an important part of the hospital operation.